Pain and the collision of expertise in primary care physical exams. (October 2019) - McArthur, Amanda
Using conversation analysis and a collection of naturally occurring US primary care consultations, this article explores the search for pain during primary care physical exams. Inhabiting this activity is a 'collision' of expertise between physicians' clinical knowledge about bodies and patients' knowledge about their bodies. I show how patients responding to questions like does that hurt? tacitly guide physicians to their pain using pain displays, glottal cutoffs and response delays to observably react to the physician's touch, delineating painful from non- or less-painful areas. Physicians respond to these practices by altering the trajectory of their touch in coordination with the patient's embodied behavior. In this local context, physicians' touch not only constrains patients to (dis)affirm pain in a particular location, but it is also a unique affordance for patients to guide physicians while nonetheless preserving the physician's authority over where to test for pain, thereby maintaining the physical examination activity framework.